The Effect of Organizational Culture And Decision Making Toward Organizational Citizenship Behavior of Teacher in Pre-School - Griet Helena Laihad; Rita Retnowati (JETL (Journal of Education, Teaching and Learning), 2018)
The research objectives are to determine the effect of Organizational Culture and Decision making toward organizational citizenship behavior  of  teacher in pre-school. The research was conducted sampling to 175 respondent teacher of pre-school at Bogor City with Path Analysis design. The results are; (1) Organizational Culture has direct influence toward Organizational Citizenship Behavior of teacher in pre-school (2) Decision making has direct influence toward  Organizational Citizenship Behavior of teacher in pre-school (3)  Organizational Culture  has direct influence toward Decision making.  Conclusion, in enhancing organizational citizenship behavior of teacher in pre-school would be strengthening on Organizational Culture and Decision making.